Poetry and Poetry Interpretation In “Devoni Foniy” - Azimov Yunus Yusupovich; Yusufzoda Shabnami Yunus (Indonesian Culture and Religion Issues, 2025)
Devoni Foniy undergoes evaluation through poetic analysis as well as interpretation because it stands as an important work from the plentiful body of early poetic literature. The investigation evaluates crucial concepts and artistic features and historic and cultural elements in the text to reveal its philosophical and historical nature. Multiple interpretive theories receive analysis through symbolical interpretations and subtle language elements which carry additional meanings. The literary and intellectual standing of Devoni Foniy emerges through assessing poetic elements and literary techniques in his work thus confirming his central role within classical and modern literary discussions.